(untitled) (Indian Internet Journal of Forensic Medicine and Toxicology, 2016)
Article 6 of the Universal Declaration of Human Rights states, “that everyone has the right to recognition everywhere as a person before law”. Therefore, every citizen of a member State of the United Nations has a right to possess his personal identity. Age is one of the key parameters to establish identity of an individual. For age estimation, among the various parameters, dental examination also provides useful information. Hence, dental age assessment (DAA) is an important task for all dentists to perform and more so after the recent amendments in the provisions related to age assessment under Juvenile Justice (Care and Protection of Children) Act (JJA) in this country (India). However, like other parameters, DAA has its limitations. This issue has been examined in light of the various court judgments on of this aspect of practice of forensic dentistry after reviewing majority of the methods used for DAA available in the literature and recommendations have been made for appropriate methods that can be used in different age groups and scenario.